Coordinated Electric Vehicle Charging for Commercial Parking Lot with Renewable Energy Sources. Issue 3 (7th February 2017) - Jhala, Kumarsinh; Natarajan, Balasubramaniam; Pahwa, Anil; Erickson, Larry
Abstract: Electric vehicles (EVs) are increasing in popularity because of their low operating cost and environmental friendly operation. The anticipated rise in EV usage, along with the increased use of renewable energy sources and smart storage devices for EV charging, presents opportunities as well as challenges. Time-varying electricity pricing and day-ahead power commitment add another dimension to this problem. In this research, we develop coordinated EV charging strategies for renewable energy powered charging stations in parking lots. This work maximizes the profits for parking lot operators by taking advantage of time-varying electricity pricing while satisfying system constraints. We propose a linear programming-based strategy for EV charging, and we specifically derive a centralized linear program that minimizes the charging cost for parking lot operator while satisfying customers' demand in available time.